Effects of Yi Jin Bang versus conventional exercise therapy in people with subacromial pain syndrome: A randomized controlled trial - Jinde Liu; Stanley Sai-chuen Hui; Yijian Yang; Cindy Hui-ping Sit (Elsevier, 2024)
Background/objective: Previous studies have indicated that mind-body exercises can reduce pain and improve function for patients with musculoskeletal conditions. Yi Jin Bang is a novel home-based Chinese mind-body Qigong exercise for shoulder pain. However, few studies have evaluated its effects on subacromial pain syndrome. This study aimed to compare the effects of Yi Jin Bang with conventional exercises for subacromial pain syndrome. Methods: Adults with subacromial pain syndrome (N = 105; mean [SD] age, 37 [16] years; 73 females [70%]; median [IQR] duration of symptoms, 12 [6-24] months) were randomly assigned to either the experimental group (n = 53) or the control group (n = 52). The experimental group performed home-based Yi Jin Bang exercises, whereas the control group performed home-based conventional exercises (stretching, strengthening, and motor control exercises). Both interventions were performed four times a week for 16 weeks. The primary outcome was the Shoulder Pain and Disability Index (SPADI). Secondary outcomes included current shoulder pain intensity, active shoulder range of motion, back scratch test, isometric shoulder strength, and health-related quality of life. Assessments were performed at baseline and weeks 4, 8, 12, and 16. The primary endpoint was week 16. Results: No significant between-group difference was observed in the SPADI score at week 16 (mean difference, Yi Jin Bang minus conventional exercise, 0.14, 95% confidence interval −2.96 to 3.24; p = 0.93). Conclusion: There were no differences between Yi Jin Bang and conventional exercises in improving pain, disability, shoulder mobility, shoulder strength, and quality of life for people with subacromial pain syndrome.